Obesity, body composition, and prostate cancer - Fowke, Jay H (BioMed Central, 2012)
BACKGROUND: Established risk factors for prostate cancer have not translated to effective prevention or adjuvant care strategies. Several epidemiologic studies suggest greater body adiposity may be a modifiable risk factor for high-grade (Gleason 7, Gleason 8-10) prostate cancer and prostate cancer mortality. However, BMI only approximates body adiposity, and may be confounded by centralized fat deposition or lean body mass in older men. Our objective was to use bioelectric impedance analysis (BIA) to measure body composition and determine the association between prostate cancer and total body fat mass (FM) fat-free mass (FFM), and percent body fat (%BF), and which body composition measure mediated the association between BMI or waist circumference (WC) with prostate cancer. METHODS: The study used a multi-centered recruitment protocol targeting men scheduled for prostate biopsy. Men without prostate cancer at biopsy served as controls (n = 1057). Prostate cancer cases were classified as having Gleason 6 (n = 402), Gleason 7 (n = 272), or Gleason 8-10 (n = 135) cancer. BIA and body size measures were ascertained by trained staff prior to diagnosis, and clinical and comorbidity status were determined by chart review. Analyses utilized multivariable linear and logistic regression. RESULTS: Body size and composition measures were not significantly associated with low-grade (Gleason 6) prostate cancer. In contrast, BMI, WC, FM, and FFM were associated with an increased risk of Gleason 7 and Gleason 8-10 prostate cancer. Furthermore, BMI and WC were no longer associated with Gleason 8-10 (OR(BMI )= 1.039 (1.000, 1.081), OR(WC )= 1.016 (0.999, 1.033), continuous scales) with control for total body FFM (OR(BMI )= 0.998 (0.946, 1.052), OR(WC )= 0.995 (0.974, 1.017)). Furthermore, increasing FFM remained significantly associated with Gleason 7 (OR(FFM )= 1.030 (1.008, 1.052)) and Gleason 8-10 (OR(FFM )= 1.044 (1.014, 1.074)) after controlling for FM. CONCLUSIONS: Our results suggest that associations between BMI and WC with high-grade prostate cancer are mediated through the measurement of total body FFM. It is unlikely that FFM causes prostate cancer, but instead provides a marker of testosterone or IGF1 activities involved with retaining lean mass as men age.